1996
DOI: 10.1051/mmm:1996109
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Layers in Copper Based Superconducting Materials

Abstract: Abstract. 2014 Recently discovered series of high Tc superconductors, characterized by the existence of two types of cations within the same layer, are presented. The first family concerns the mercury based cuprates, Hg1-xMxA2Cam-1CumO2m+2+03B4, with A = Ba and/or Sr, which exhibit structures closely related to that of the thallium cuprates TlBa2Cam-1CumO2m+3. They differ from the thallium cuprates by a high oxygen deficiency at the level of the mercury layer. It is shown that cations such as M = Cu, Pb, Tl, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 49 publications
0
10
1
Order By: Relevance
“…These results suggest that the transition elements are located on both the Tl and the Cu positions, particularly for Nb-and Ta-based samples. This behavior is different from the results observed for M"Mo (11) (Mo is only substituting for Tl), as well as from the results in Cr-based compounds which form chromate groups exhibiting long-range ordering with the thallium polyhedra, similar to those observed in the carbonate groups in the 1201 phases (see (21) for a review). It should be noted that there is always a small cation deficiency since M#Tl+0.9, but this is not unusual for thallium-based layered cuprates.…”
Section: The Average Structure: X-ray Analysis and Edscontrasting
confidence: 65%
“…These results suggest that the transition elements are located on both the Tl and the Cu positions, particularly for Nb-and Ta-based samples. This behavior is different from the results observed for M"Mo (11) (Mo is only substituting for Tl), as well as from the results in Cr-based compounds which form chromate groups exhibiting long-range ordering with the thallium polyhedra, similar to those observed in the carbonate groups in the 1201 phases (see (21) for a review). It should be noted that there is always a small cation deficiency since M#Tl+0.9, but this is not unusual for thallium-based layered cuprates.…”
Section: The Average Structure: X-ray Analysis and Edscontrasting
confidence: 65%
“…The electron diffraction investigation showed that the three structural types of oxycarbonates are stabilized: -For 0 Յ y Ͻ 1.8, a [S 2 CC] 1 [1201] structure is obtained. The subcell is tetragonal with a ϭ a p and c Ȃ 16.5 Å and P-type symmetry.…”
Section: Previous Results On the Synthesis And Homogeneitymentioning
confidence: 99%
“…This oxycarbonate exhibits an orthorhombic supercell with a Ȃ a p , b Ȃ 8a p , c Ȃ 17 Å and A-type symmetry. The superstructure along b results from the periodic formation, in the [S 2 CC] 1 [1201] structure, of (100) crystallographic shear planes (CSP), every four octahedra ( Fig. 1b and c Varying the Ba/Sr ratio, a third family has been observed, which only differs from the second family by the orientation and the periodicity of the CSPs, which are (110) planes ( Fig.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations